Controllable Fabrication of Ordered Mesoporous Bi2WO6 and Its High Photocatalytic Activity under Visible Light - Xueming Dang; Xiaoli Dong; Hua Wang; Xiufang Zhang; Hongchao Ma; Mang Xue (International Journal of Photoenergy)
Ordered mesoporous Bi2WO6 was fabricated by nanocasting technique using SBA-15 as the template. The effect of the dosage of SBA-15 on the formation of the ordered structure and the photocatalytic ability of mesoporous Bi2WO6 was discussed. It was confirmed that the ordered mesoporous structure was obtained as the dosage of SBA-15 was 0.3 g. It was found that, compared to Bi2WO6, the RhB degradation rate with ordered mesoporous Bi2WO6 was enhanced under visible light (λ>400 nm) by the photocatalytic measurements. The enhanced photocatalytic performance of ordered mesoporous Bi2WO6 was attributed to its particular ordered mesoporous structure which could increase the light-harvesting efficiency, reduce the recombination of the photogenerated charge carriers, and promote the surface reaction.